A proposed role for endomembrane trafficking processes in regulating tonoplast content and vacuole dynamics under ammonium stress conditions in Arabidopsis root cells - Robert, German; Yagyu, Mako; Lascano, Hernan Ramiro; Masclaux-Daubresse, Céline; Yoshimoto, Kohki (Taylor and Francis, 2021)
Ammonium (NH4+) stress has multiple effects on plant physiology, therefore, plant responses are complex, and multiple mechanisms are involved in NH4+ sensitivity and tolerance in plants. Root growth inhibition is an important quantitative readout of the effects of NH4+ stress on plant physiology, and cell elongation appear as the principal growth inhibition target. We recently proposed autophagy as a relevant physiological mechanisms underlying NH4+ sensitivity response in Arabidopsis. In a brief overview, the impaired macro-autophagic flux observed under NH4+ stress conditions has a detrimental impact on the cellular energetic balance, and therefore on the energy-demanding plant growth. In contrast to its inhibitory effect on the autophagosomes flux to vacuole, NH4+ toxicity induced a micro-autophagy-like process. Consistent with the reduced membrane flux to the vacuole related to macro-autophagy inhibition and the increased tonoplast degradation due to enhanced micro-autophagy, the vacuoles of the root cells of the NH4+-stressed plants showed lower tonoplast content and a decreased perimeter/area ratio. As the endosome-to-vacuole trafficking is another important process that contributes to membrane flux toward the vacuole, we evaluated the effects of NH4+ stress on this process. This allows us to propose that autophagy could contribute to vacuole development as well as possible avenues to follow for future studies.